Correlation between visual scores and parathyroid function - Lorente-Poch, Leyre; de Miguel-Palacio, Maite; Sancho-Insenser, Joan (Frontiers in Endocrinology, 2023)
This mini review summarizes the controversies regarding routine parathyroid identification reviews publications that assess visual scores to predict parathyroid function after thyroidectomy during the pre-ICG era.